(untitled) (Nóema, 2013)
A proper reflection about the music in the masses era can develop itself only if it’s interwoven with the media totalitarianism which seems to be the fate of our times. Beyond the ideology and the fashion of “contamination” that leeds towards a levelling of values, it’s much better to sharpen instead the real difference between the distinct practices of listening, without academic prejudices but also without misleading homologations. Neither puritanisms nor false transgressions: classical music and pop music must be received iuxta propria principia, each of them along its own specific language.